Analysis of the Effectiveness of Implementing Guidance and Counseling Services at SMPIT ‘Abdan Syakuro Lampu Iman - Arya Wiradarma Saputra; Azzahra Arrohma; Fairuz Sausan Kamil; Fitria Nursani Rofifah Supriyadi; farida, Nur Aini (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2025)
Observation of Guidance and Counseling at SMPIT ‘Abdan Syakuro Lampu Iman aims to enable compilers to know and understand the implementation of BK services, ongoing programs at schools as well as supporting and inhibiting factors while BK services and programs are running. The data collection technique of this study used observation techniques and semi-structured interviews. The interviewees included a BK teacher and two 9th grade students. Based on the results of interviews with BK teachers and service students provided by Guidance and Counseling at the school, there are three services, namely personal services, social services and academic services. In order for this service to run effectively, BK teachers collaborate with homeroom teachers to work together to serve students' guidance and counseling needs. One of the challenges for BK teachers is that there are some students who are less cooperative with BK teachers. As for the statements of BK service students at SMPIT ‘Abdan Syakuro, it has gone well, such as serving students who want to consult on personal and other issues and helping students to develop their potential interests and talents. Overall, BK services at this school function well as a tool to develop students' potential and overcome problems, with the hope that they can continue to be optimized through a more intensive approach and ongoing cooperation